The ketogenic diet in disease and development. Issue 68 (August 2018) - Barry, Denis; Ellul, Sarah; Watters, Lindsey; Lee, David; Haluska, Robert; White, Robin
Highlights: The ketogenic diet is effective in treating multiple neurological disorders, including epilepsy. A ketogenic diet during pregnancy alters the developing brain and postnatal behaviour. The consequences of a material ketogenic diet on the developing brain are not fully understood. Abstract: The ketogenic diet, low in carbohydrates and high in fat, was initially designed to reduce seizure onset in epilepsy. More recent evidence has shown its effectiveness in the treatment of movement and psychological disorders, and in general health maintenance. The cellular significance of ketone body metabolism during development and in the adult central nervous system is being revealed; however, the effects of replacing glucose with ketone bodies as the brain's primary energy source especially in pregnancy are not fully understood. In this mini-review, we highlight key findings related to the functional consequences of ketone body metabolism and monocarboxylic transporter expression throughout development and adulthood. We outline the therapeutic relevance of ketone bodies, and place a spotlight on the known effects of a maternal ketogenic diet on the developing brain.